Diversifikasi Produk dan Inovasi Kemasan Pupuk Organik Granular dari Limbah Kotoran Kambing untuk Meningkatkan Daya Saing Petani Desa Karangharjo - Khozin, Mohammad Nur; Aultavia, Reza Novita; Alfarizi, Zulfikar Ahmad; Soeparjono, Sigit; Habriantono, Bakhroini; Wagiyana; Soeharto; Alfarisy, Fariz Kustiawan; Purnamasari, Listya (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
The problem of fertilizer scarcity and the high cost of chemical fertilizers are major challenges for farmers in Karangharjo Village, Silo District, Jember Regency. This community service program aims to increase the competitiveness of local products through product diversification and packaging innovation of granular organic fertilizer made from goat manure waste with the addition of Trichoderma sp. The implementation method includes socialization and education, discussion forums, granular organic fertilizer product diversification activities, introduction and demonstration of product packaging. The results of the activity show an increase in farmers' knowledge and skills in utilizing livestock waste into quality fertilizer packaged in economical sizes. This innovation not only overcomes fertilizer limitations, but also opens new economic opportunities and strengthens the competitiveness of organic fertilizer products in a sustainable manner. This activity is well received by farmers and is expected to continue.